Impact of Mobile Applications on Improving Healthy Lifestyle of Patients with Metabolic Syndrome: A Systematic Review - Nafisah, Nafisah; Sri Hayati, Yati (Indonesian Journal of Human Nutrition, 2023)
Metabolic syndrome (MetS) generally occurs in adults and becomes more prevalent with age. Most e-health tools are often described as web-based platforms or applications designed for the general public, rather than specifically for MetS patients. Mobile applications, however, have great potential in providing internet-based health education and supporting the self-management of MetS patients, particularly in diet management and physical activity. This study aimed to synthesize the findings on the impact of mobile app interventions in enhancing self-management practices among MetS patients. A comprehensive literature search covering the years 2019 to 2023 was conducted across Science Direct, ProQuest, and PubMed databases. From 16,628 articles analyzed, 11 were selected for review. The interventions were categorized into short-term (> 12 months) and long-term (≥ 12 months). Eleven mobile applications were identified. These applications were primarily free and designed to facilitate the management of diet and physical activity. The study observed significant changes in the components of metabolic syndrome, including weight, blood pressure, waist circumference, body mass index, fasting blood sugar, triglycerides, and High-Density Lipoprotein cholesterol. Furthermore, these mobile applications demonstrated a positive impact on the lifestyle of MetS patients, influencing factors such as eating behavior, physical activity, self-efficacy, sleep quality, and sleep duration.